The applications of a psychospiritual model in the helping professions : principles of innerview guidance - Speyer, Cedric; Yaphe, John (New York, NY : Routledge, 2021)
"This book brings together the historically separate domains of mental health and spiritual awareness in a holistic framework called InnerView Guidance. Building on strength-based and solution-oriented approaches to therapy, the InnerView model offers a unique psychospiritual approach which can be applied in any of the helping professions. InnerView recognizes the individual's need for internal cohesion between psychological growth and spiritual development. It is a principle-driven paradigm that foregrounds 'soul work' as a central evolutionary task. The book presents the core concepts and methodology involved in the alignment of ego with soul. Chapters explain the theoretical roots of the model, explore practical applications in therapeutic settings, and introduce InnerView as a rich synergy of psychotherapy and spiritual guidance. Taking an original and cutting-edge approach, this valuable text will be essential reading for scholars and students, as well as practitioners in the fields of psychotherapy, counselling, life coaching, social work, and spiritual care"--
Introduction : InnerView landscapes : overview of new horizons in psychology -- The presenting person : from treating problems to freeing persons -- Living in a bigger story : life stories re-envisioned as soul journeys -- The 4Fold path : a psychospiritual map for navigating personhood -- The matryoshka method : an inside-out approach to clinical process -- InnerView attunement : the healing bond in therapeutic practice -- The principles in practice : InnerView applied by helping professionals -- Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Mental illness -- Alternative treatment; Psychotherapy -- Religious aspects; Psychiatry and religion; PSYCHOLOGY / Psychotherapy / Counseling; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Movements / Transpersonal